Impact of digital entrepreneurship in Malaysia in the era of Covid-19 pandemic - Gunaseelan, Khemaalatha; Subramaniam, Tamil Selvan; Lai, Chee Sern; Jabor, Mohd Khata; Rathakrishnan, Geetha (Human Resource Management Academic Research Society, 2022)
The pandemic of COVID-19 has constrained the retail outlets of the country to stay shut. Malaysia seen the pandemic has trigger positive open door in digitalization in internet shopping and food dealing with administration. Hence, this study aims to investigate “What are the impact of digital entrepreneurship in Malaysia in the era of Covid-19 pandemic?”. Meanwhile the objective of this study is to ‘Identify the impact of digital entrepreneurship in Malaysia during Covid-19 pandemic’. This research uses qualitative methods with a descriptive analysis approach and contextual techniques. For the finding, we can conclude that there is a positive impact on digital entrepreneurship on Malaysian society during Covid-19. COVID-19 pandemic had turned conventional shopping and it needed to challenge individuals into new standards rehearses.